The Corelation between Mother’s Responsive Feeding and Picky Eater Events and Nutritional Status of Children Aged 1 to 5. - Devanti Miftahul Jannah; Sunanto; Nur Hamim (YAYASAN PENDIDIKAN MANDIRA CENDIKIA, 2023)
Children are said to be an investment and hope in the future of the nation who will become the next generation in the future. This research aims to identify mothers' responsive feeding, identify picky eater problems, identify nutritional status, analyze the corelation between mothers' responsive feeding and picky eaters and children's nutritional status. ages 1 year to 5 years in Kedawung Village. The method used descriptive analytic with a cross sectional study design. The research had a sample of 55 children with the total sampling technique used. Data analysis used the Chi Square Test. The results of the analysis in this study were that 22 people (53.7%) rarely implemented maternal responsive feeding for children aged 1 year to 5 years in Kedawung village, while 19 mothers (46.3%) often did it. The problem of picky eaters in children aged 1 year to 5 years. In Kedawung village there are 29 toddlers (70.7%), while there are 12 toddlers who are non-picky eaters (29.3%). The nutritional status of children aged 1 year to 5 years in Kedawung village experienced malnutrition as many as 16 toddlers (39.0%), malnutrition 14 toddlers (34.1%), normal nutrition 11 toddlers (26.9%). There is a corelation between mother's responsive feeding and picky eater and the nutritional status of children aged 1 year to 5 years in Kedawung village with ρ = 0.022 (ρ < α).